Histological examination of the interspinous ligament in horses with overriding spinous processes. (February 2019) - Ehrle, A.; Ressel, L.; Ricci, E.; Merle, R.; Singer, E.R.
Highlights: Interspinous ligaments in horses with overriding (dorsal) spinous processes (ORSPs) show loss of structure and integrity. Fibrocartilaginous metaplasia was identified in the interspinous ligaments of horses with ORSPs. Numbers of sensory nerves in interspinous ligaments of horses with ORSPs were significantly increased compared to controls. Abstract: The equine interspinous ligament (ISL) consists of an oblique crossing arrangement of collagenous bundles which are thought to counteract the tensile and rotational forces of distraction between the spinous processes (SPs) in the caudal thoracic and cranial lumbar spine. The aim of this controlled histological study was to assess the structural anatomy and innervation of the ISL in horses with clinically significant overriding (dorsal) SPs (ORSPs) and to compare the findings with the ISL of normal horses. Samples of the ISL were obtained from 10 horses that underwent subtotal ostectomy for treatment of ORSPs. Control samples were obtained from horses without spinal pathology. Histological staining of ISL sections with haematoxylin and eosin was performed to assess the morphology of the ligaments and with Alcian blue-periodic acid-Schiff to determine the proteoglycan and glycosaminoglycan content. Immunohistochemistry for S100 was performed for quantitative evaluation of nerves within the ISL. The ISL in horses with ORSPs had an altered collagen fibre alignment and arrangement of the ligamentous layers when compared to healthy controls. A significant increase in fibrocartilaginous tissue with evidence of fibrocartilaginous metaplasia was detected ( P  = 0.001). The number of nerves in the ISL samples was significantly higher in horses with ORSPs than in controls ( P  = 0.017). Structural alterations of the ISL, including loss of fibre alignment and fibrocartilaginous metaplasia, are associated with ORSPs in the equine thoracolumbar spine. In addition, an increase in innervation of the ISL in horses with ORSPs, compared to normal, may explain the thoracolumbar pain experienced by some horses with ORSPs.